Features of the dynamics of serum C-reactive protein and IL-6 concentrations in case of experimental carrageenan-induced inflammation of temporomandibular joints - D.O. Kovalchuk; N.M. Savielieva; A.Yu. Nikonov; N.M. Breslavets (Journal of V. N. Karazin Kharkiv National University: Series Medicine, 2025)
Background. The temporomandibular joint is a complex anatomical and functional structure, consisting of the mandibular condyle, mandibular fossa, articular tubercle of the temporal bone, intra-articular disc, and joint capsule. Temporomandibular joint movements are carried out through the highly coordinated activity of all its components, primarily the masseter muscles, which are controlled by the nervous system.